(3CfehPL GdYdhes - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeMehO ai cd aYGdg hHYO jbhd GdabjQ GdOhGfi s
(3BNQgG (B:s
(3gPG BNQ eG bUOJ GjQGOg ai gPg GdQSGdI LYdJg GfehPLkG dJdc GdYdhe hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdNGeSs
(3GfXQ GdeNWhW Qbe (B259s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
(3cdjI GdMbhb (B(112 - (3H(B) s
Keywords: (3GdeYGQa GdYGeIs